Functional Properties of Cartilaginous Tissues Engineered From Infrapatellar Fat Pad Derived Mesenchymal Stem Cells. - Kelly, Daniel; Buckley, Conor (My University, 2010)
Articular cartilage has a poor intrinsic capacity for self-repair. The advent of autologous chondrocyte implantation has provided a feasible method to treat cartilage defects. However, the associated drawbacks with the isolation and expansion of chondrocytes from autologous tissue has prompted research into alternative cell sources such as mesenchymal stem cells (MSCs) which have been found to exist in the bone marrow as well as other joint tissues such as the infrapatellar fat pad (IFP), synovium and within the synovial fluid itself. In this work we assessed the chondrogenic potential of IFP-derived porcine cells over a 6 week period in agarose hydrogel culture in terms of mechanical properties, biochemical content and histology. It was found that IFP cells underwent robust chondrogenesis as assessed by glycosaminoglycan (1.47+/-0.22% w/w) and collagen (1.44+/-0.22% w/w) accumulation after 42 days of culture. The 1Hz dynamic modulus of the engineered tissue at this time point was 272.8kPa (+/-46.8). The removal of TGF-beta3 from culture after 21 days was shown to have a significant effect on both the mechanical properties and biochemical content of IFP constructs after 42 days, with minimal increases occurring from day 21 to day 42 without continued supplementation of TGF-beta3. These findings further strengthen the case that the IFP may be a promising cell source for putative cartilage repair strategies.
PUBLISHED
PMID: 20005518
Keywords: Cartilage repair; agarose hydrogel; Mesenchymal Stem Cells; infrapatellar fat pad; functional tissue engineering; Next Generation Medical Devices